2006
DOI: 10.1021/je060068f
|View full text |Cite
|
Sign up to set email alerts
|

Critical Temperatures and Pressures of 12 Phthalates Using the Pulse-Heating Method

Abstract: The critical temperatures and pressures of phthalates with the straight side alkyl chains C 6 H 4 -1,2-[COO(CH 2 ) n H] 2 (n is from 1 to 11) as well as bis(2-ethylhexyl) phthalate have been measured. No literature data are available for the critical properties of phthalates. Since phthalates decompose at temperatures well below their critical temperatures, the method of pulse heating of a wire probe immersed into the liquid under study has been used. The method minimizes the effect of thermal decomposition be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…In this interval, the apparent critical temperatures and pressures did not depend on the heating time. The uncertainties in the critical temperatures and pressures measured by the pulse-heating method were discussed in our previous paper . We estimate the uncertainties for esters studied at 0.01 T c and 0.03 p c .…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…In this interval, the apparent critical temperatures and pressures did not depend on the heating time. The uncertainties in the critical temperatures and pressures measured by the pulse-heating method were discussed in our previous paper . We estimate the uncertainties for esters studied at 0.01 T c and 0.03 p c .…”
Section: Methodsmentioning
confidence: 92%
“…The uncertainties in the critical temperatures and pressures measured by the pulseheating method were discussed in our previous paper. 21 We estimate the uncertainties for esters studied at 0.01 T c and 0.03 p c .…”
Section: Measurement Of the Critical Temperatures And Pressuresmentioning
confidence: 99%
“…The uncertainties of the critical properties measured by the pulse-heating method were discussed in detail in our previous papers [9,10,15]. It has been shown that the uncertainties are dp c ¼ 0:03p c , dT c ¼ 0:01T c for low-molar-mass compounds and dp c ¼ 0:04p c , dT c ¼ 0:015T c for compounds with high acentric factors x !…”
Section: Uncertaintiesmentioning
confidence: 97%
“…The uncertainties of the critical properties measured by the pulse-heating method have been discussed in detail elsewhere. ,, For alkyl glycolates studied, the relative combined expanded uncertainties with the 0.95 level of confidence are U r ( T c ) = 0.01 and U r ( p c ) = 0.03.…”
Section: Experimental Sectionmentioning
confidence: 99%